KEBERADAAN DOKTER AHLI KANDUNGAN LAKI-LAKI DALAM TINJAUAN HUKUM ISLAM - Khairul Fahmi S (Yayasan Pendidikan Islam dan Multikultural, 2022)
In Islamic law, the relationship between patients and doctors is the relationship between service users and service sellers, so that there is an ijrah contract between the two parties. Patients can take advantage of the knowledge and skills of doctors, while doctors can receive rewards from their profession, such as in the profession of male obstetricians in the perspective of Islamic law. Health care is one of the public places where all people will interact there. These include hospitals, health centers, and others. A hospital is a professional health care institution whose services are provided by doctors, nurses, and other health professionals. It is in such health care facilities that the boundaries between male and female genitalia according to Islam will be set aside, meaning that in the sentence just now the hijab is blurred between men and women who are not married. Therefore, the author will review the Islamic law regarding the existence of male obstetricians.